Quality evaluation of fermented products of various local agroindustrials by-products: the effect on digestibility and growth performance of common carp juvenile - Suprayudi, Muhammad Agus; Edriani, Gebbie; Ekasari, Julie (Indonesian Society of Scientific Aquaculture (ISSA), 2012)
The aim of this research was evaluating the quality and digestibility of fermented local feedstuff as well as its effect on growth performance of common carp Cyprinus carpio juvenile. The local feedstuffs tested in this experiment were kapok seed, cassava peel, copra, rubber seed, and palm kernel meal. The previously milled feedstuff was fermented with instant yeast Saccharomyces cerevisiae with a dose of 0.9% w/w and incubated for 24 hours. Following this, the fermented feedstuffs were dried, mixed with reference diet with a ratio of 3:7 and supplemented with 0.5% Cr2O3 as digestibility test indicator. Common carp juveniles with an initial average body weight of 14,11±1,28 g were cultured for 30 days. Fish feces were collected since the 6th day of culture, and followed by laboratory analyses. The results show that fermentation could increase the crude protein content of feedstuff with a range of 16.85‒31.11%, and decrease crude fiber with a range of 2.45‒31.65% with the exception of copra. Furthermore, fermentation also increased the feed digestibility including protein, energy, and total digestibility by the tested fish, as it is shown that the use of fermented feedstuffs may increase protein digestibility 3.88‒11.73%, 2,21‒10,24%, and 3,63‒72,37%. Finally, it can be concluded that fermentation can increase the digestibility of feed with local ingredients by common carp juvenile. Keywords: fermentation, digestibility, local materials, common carp